Fit to practice empire, race, gender, and the making of British medicine, 1850-1980 - Haynes, Douglas Melvin (University of Rochester Press, 2017)
Traces the history of the British General Medical Council to reveal the persistence of hierarchies of gender, national identity, and race in determining who was fit to practice British medicine
Title from publisher's bibliographic system (viewed on 21 May 2021)
Keywords: Geschichte 1850-1980; Medicine / Great Britain / History / 19th century; Medical policy / Social aspects / Great Britain; Discrimination in medical care / Great Britain; Medicine / Great Britain / History / 20th century; Medizin; Diskriminierung; Heilberuf; Großbritannien